SLAB reinforced with HDPE pipe (SREHP) - Ahmad Bukhari, Abdullah (2014)
Reinforced slab are used in floors and walls of building for construction work. The floor system of a structure can take many forms such as in situ solid slab and pre-cast unit. Steel is common reinforcement material used comprehensively for construction today. High Density Polyethylene (HDPE) as thermoplastic polymer matrix systems can be introduced as an alternative replacement material for steel as structural elements to overcome the common conventional materials' problems. The slab reinforced with HDPE pipe (SREHP) will be test using third-point load test was adopted to assess this study. For this test, we can get the flexure strength and deflection of SREHP to compare with conventional slab. The result for this testing shows that, HDPE is not good to be used as replacement material. It will reduce the strength and increase the deflection. Besides that, the tensile test show the strain of HDPE was weak to compare with steel reinforcement. The HDPE pipe has proved that, the mechanical characteristics that is suitable for light structural element and should be comparing with another material. Furthermore, HDPE pipe also probably generate a new product by changing the type of conventional reinforcement slab to hollow reinforcement slab. HDPE pipe still can be applied in lightweight structure in the future such as lightweight slab as it can withstand a small load.